SMEs Management in the Tourism Sector - Roxana SARBU; Cristina ALPOPI; Mihai DINU; Stefan Gabriel BURCEA; Ovidiu Andrei Cristian BUZOIANU (Communications of International Proceedings, 2021)
Tourism is one of the most dynamic economic sectors, which is experiencing permanent changes and an upward trend. Knowing the trends, the challenges facing world tourism, the determinants that will influence the international tourism activity in the coming period, the forms of tourism that will record high growth rates in the first part of the XXI century, must be taken into account. by local and central public administration authorities when developing tourism development policies, strategies, plans and programs. The appreciation of tourism as a service activity results not only from its content, but also from the particularities of the tourist service, from the elements that outline a specific specific from other services belonging to the tertiary sector. Therefore, the tourist product, as a component of the tourist offer, is considered to be the result of associations, interdependencies between resources and services. This reality motivates the overwhelming importance of the services, of the fact that in the contouring and particularization of the tourist products, the center of gravity falls on the activity of services.
Keywords: Development; IMM; management; tourism